BANK WASTE AS MANAGEMENT OF HOUSEHOLD RUBBER BASED ON COMMUNITY - Aisyah Fadilah (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2018)
The level of population, the increasing of welfare and lifestyle also community habits such as dumping waste into rivers build up the complex of waste problems, especially health impacts. Therefore, the need for waste management efforts involving community participation. The purpose of this study is to analyze the implementation of community-based waste management RW 05 Bungursari one with the Garbage Bank. Waste bank begins with the process of sorting organic and inorganic waste. Then the inorganic garbage that has been sorted is collected in the Bank Trash Unit to do the weighing and recording of the sale proceeds in the savings book system such as banking. The method used in this research surveys. Data collection is done by direct interview to the respondent, that is driving the activity of waste management at the location. Data analysis was done descriptively qualitative. The research was conducted in RW 05 Bungursari Kecamatan Cibeunying Kidul Kelurahan Pasir Layung Kota Bandung. Community-based waste management of RW 05 Bungursari Trash Bank is done by involving the participation of RW 05 Bungursari women. Community-based waste management such as Waste Bank can minimize garbage problems and can increase economic independence. Community-based waste management such as Waste Banks needs to be further socialized in order for more citizens to be involved in Waste Bank activities as well as the need for partnership support between Waste Bank management residents and related stakeholders.